Effect of processing conditions and catalyst type on the thermal oxidative degradation mechanisms and melt stability of metallocene and Ziegler‐catalyzed ethylene‐1‐hexene copolymers. Issue 2 (13th November 2021) - Al‐Malaika, Sahar; Daraz, Umar; Issenhuth, Sylvie
Abstract: Polyolefins have traditionally been polymerized via the heterogeneous Ziegler Natta (Z‐N) catalysts since their discovery in the 1950s, but the later developments of the homogeneous single site metallocene/methylaluminoxane (MAO) catalysts have opened the possibility for the synthesis of polyolefin polymers and copolymers (commercialized in the 1990s) with highly defined microstructure and great degree of control of their molecular architecture resulting in some unique beneficial properties compared to their Z‐N counterparts. The main aim of the work reported here was to examine critically the effects of the processing conditions during multipass extrusions on the molecular and rheological characteristics of metallocene‐catalyzed linear low density polyethylene and a Ziegler‐Natta‐based counterpart polymer and on the thermoxidative (in the melt) stability of their melts and their stabilization. Both polymers examined here were based on ethylene‐1‐hexene copolymers and produced by the same manufacturer with similar density and melt index (MI) values. The melt stability and rheological properties of the polymers were determined from melt flow and capillary rheometric measurements. The molecular characteristics were investigated using GPC for molecular weight determination, 13 C‐NMR for short chain branching, 1 H‐NMR and FTIR for the type and concentration of unsaturation groups, FTIR for carbonyl‐containing compounds and chemical analysis for hydroperoxide determination. The processibility of the two polymers was compared through examination of different processing conditions (die temperatures 210–285°C, screw speeds 50–200 rpm) used for a multipass extrusion process. Further, the effects of the processing conditions on the melt thermoxidation of the differently catalyzed LLDPE polymers were investigated. The results demonstrated that both the catalyst type and the processing conditions have a great effect on both the rheological and the themoxidative behavior of the polymers as well as on the balance between the competing oxidative reactions taking place in the polymer melt, for example, chain scission and crosslinking reactions. The results obtained for the different multipass extrusion conditions of the two polymers have illustrated clearly that the degradation mechanisms during their melt processing are substantially different. The melt degradation route of the Ziegler‐catalyzed polymer was shown to be dominated by chain scission reactions under all the processing conditions examined, and more so at the higher shear rates and temperatures. By contrast, the evidence clearly showed that the metallocene‐catalyzed polymer gave rise to crosslinking reactions that predominated even under the more severe processing conditions, that is, higher temperatures and shear rates. Abstract :